Programas PNAIC, ABC e Educa Juntos: Um olhar para a alfabetização - Muller, Marineide Aparecida (2023)
The current literacy movement in Brazil has been shaped by significant changes in Public Literacy Policies since the Federal Constitution of 1988. In 2001, through Federal Law No. 10.172 of January 9, 2001, which approved the National Education Plan, a complex and sometimes contradictory scenario regarding literacy in Brazil emerged. The goal of educating all children and addressing the alarming illiteracy rate in the country is not recent. However, programs and policies have been subject to criticism due to significant divergences and discontinuity.This research aims to analyze the convergences and divergences among the following programs: "Programa de Alfabetização na Idade Certa" (PNAIC), "Alfabetização Baseada na Ciência" (ABC), and "Educa Juntos." The study aims to contribute with analyses and reflections, assisting administrators and teachers in comprehending the purposes of Literacy Programs in the teaching and learning process, enabling critical analyses of public literacy policy proposals. The study demonstrates that the programs have specificities that indicate a lack of continuity in actions, characterizing them as government policies rather than state policies.